Voltage Spectral Structure as a Parameter of System Technical Diagnostics of Ship Diesel Engine-Synchronous Generators - Gasparjans, Aleksandrs; Terebkovs, Aleksandrs; Zhiravetska, Anastasia (Electrical, Control and Communication Engineering, 2015)
A method of technical diagnostics of ship diesel engine – generator installation – is proposed. Spectral-power diagnostic parameters of the synchronous generator voltage and currents are used. The electric machine in this case is the multipurpose sensor of diagnostic parameters. A judgment on the quality of the operational processes in diesel engine cylinders and its technical condition is possible on the basis of these parameters. This method is applicable to piston compressor installations with electric drive. On the basis of such parameters as rotating torque, angular speed and angular acceleration it is possible to estimate the quality of the operating process in the cylinders of a diesel engine, the condition of its cylinder-piston group and the crank gear mechanism. The investigation was realized on the basis of a diesel-generator with linear load. The generator operation was considered for the case of constant RL load. Together with the above mentioned, the condition of bearings of synchronous machines, uniformity of the air gap, windings of the electric machine were estimated during the experiments as well. The frequency spectrum of the stator current of the generator was researched and analyzed. In this case the synchronous machine is becoming a rather exact multipurpose diagnostic sensor. The signal of non-uniformity in the operation process of diesel engine cylinders and its technical condition is the increasing of the amplitudes of typical frequencies.